Building Knowledge Sharing Intention with Interpersonal Trust as a Mediating Variable - Elianto, Whisnu; Wulansari, Nury Ariani (Jurnal Manajemen Teknologi, 2016)
Abstract. Knowledge sharing is a key aspect of knowledge management activities. The purpose of this study is to investigate the effect of personal competence on knowledge sharing intention which mediated by interpersonal trust. The data were collected from student's Postgraduate Program Universitas Negeri Semarang as many 146 in numbers. Analysis path was proposed for measuring effect of cultural intelligence and self-efficacy on knowledge sharing intention. The role of interpersonal trust as mediation was being measured too. The results show that the cultural intelligence which is owned by an individual will lead to trust among individuals and then to share one's knowledge, also the person who have self-efficacy will increase his desire to share knowledge with fellow students. All hypothesis supported except cultural intelligence, which was unsupported affect the willingness to share knowledge.Keywords: cultural intelligence, self-efficacy, interpersonal trust, knowledge sharing intention.Abstrak. Proses berbagi pengetahuan merupakan aspek kunci dalam manajemen pengetahuan. Penelitian ini bertujuan untuk mengetahui pengaruh kompetensi individu dan kepercayaan pada keinginan berbagi pengetahuan. Data dalam penelitian ini diambil dari mahasiswa Pascasarjana Unnes sebanyak 146 mahasiswa. Model analisis jalur diajukan guna melihat pengaruh kecerdasan budaya dan efikasi diri secara langsung pada keinginan berbagi pengetahuan. Peran mediasi kepercayaan antar individu diukur untuk menjadi perantara hubungan tidak langsung. Hasil menunjukkan bahwa kecerdasan budaya yang dimiliki oleh seorang individu akan menimbulkan kepercayaan antar individu untuk saling berbagi pengetahuan dan efikasi diri seseorang akan meningkatkan keinginannya untuk berbagi pengetahuan dengan sesama mahasiswa. Semua hipotesis terdukung kecuali kecerdasan budaya yang tidak terdukung mempengaruhi keinginan berbagi pengetahuan.Kata Kunci: kecerdasan budaya, efikasi diri, kepercayaan antar individu, keinginan berbagi pengetahuan.